Liver X Receptors (LXRs) in cancer-an Eagle’s view on molecular insights and therapeutic opportunities - Ramalingam, Prasanna Srinivasan; Elangovan, Sujatha; Mekala, Janaki Ramaiah; Arumugam, Sivakumar (Frontiers in Cell and Developmental Biology, 2024)
Cancer has become a serious health burden that results in high incidence and mortality rates every year, mainly due to various molecular alterations inside the cell. Liver X receptors (LXRs) dysregulation is one among them that plays a vital role in cholesterol metabolism, lipid metabolism and inflammation and also plays a crucial role in various diseases such as obesity, metabolic dysfunction-associated fatty liver disease (MAFLD), cardiovascular diseases, Type 2 diabetes, osteoporosis, and cancer. Studies report that the activation of LXRs inhibits cancer growth by inhibiting cellular proliferation, inducing apoptosis and autophagy, regulating cholesterol metabolism, various signalling pathways such as Wnt, and PI3K/AKT, modulating the expression levels of cell-cycle regulators, and promoting antitumor immunity inside the tumor microenvironment. In this review, we have discussed the role, structure, and functions of LXRs and also summarized their ligands along with their mechanism of action. In addition, the role of LXRs in various cancers, tumor immunity and tumor microenvironment (TME) along with the importance of precision medicine in LXR-targeted therapies has been discussed to emphasize the LXRs as potent targets for the development of novel cancer therapeutics.